Pemilihan Prioritas Aspek Penunjang Keberlanjutan Usaha Pada Industri Kreatif Kerajinan Daur Ulang Kertas Koran Dengan Metode Ahp (Studi Kasus: Cv. Bina Usaha Mandiri) - Arishandi, Aldy, Much. Djunaidi, S.T., M.T, Ratnanto Fitriadi, S.T., M.T (2015)
Creative industries that are part of the creative economy, which has long been a concern by the government, since the formation of Indonesian Creative Economy Development Plan in 2025, with the role of the creative industries that is growing from year to year with a contribution to the regional and national economy. As one of the creative industries driving the economy of surrounding communities Surakarta, CV. Bina Usaha Mandiri use waste newsprint obsolete become a handicraft products. But in the middle of its development, recycled newsprint industry is still constrained by a number of orders which fluctuate due to the type of product produced less meet consumer tastes, as well as the resulting production capacity is still limited. In order to support CV. Bina Usaha Mandiri to maintain the sustainability of its business, the necessary management and business development in the future, which focuses on a few aspects that support the sustainability of a business. With the aim to maintain business sustainability, this study used decision support system AHP (Analytical Hierarchy Process) to select the best alternative solutions for the sustainability of the industry.